The case of Sinaran Construction Bhd (SCB) - Wong, Foong Yee; Ibrahim, Yaakob; Hassan, Muhammad Ali (Universiti Putra Malaysia Press, 2008)
The case illustrates a scenario at Sinaran Construction Bhd (SCB) during the construction of Kuala Lumpur Convention Centre. It begins amidst a weekly progress meeting of all the project managers, about the project being three months behind schedule. The case then focuses on among others, the cause of the delay which was mainly human resource. The company reported an increase in employee turnover rate which rooted from poor working conditions, no job satisfaction, better offers elsewhere and no clear directions from superiors. Characters in the case were briefly described exposing more internal issues that needs to be resolved.